Analytical simulations for rate type nanomaterial stretching flow with dual convection - Manzoor Ahmad; Sami Ullah Khan; Syeda Quratulain; Adnan; M. Waqas; Hakim AL Garalleh; Nurnadiah Zamri; Dilsora Abduvalieva; Manish Gupta (Partial Differential Equations in Applied Mathematics)
Owing to high thermal performances and stable properties, multiple applications of nanomaterials have been studied in different industrial and engineering processes. Ongoing continuous research in nanofluid suggested different applications of nanomaterials in catalysis, aerospace engineering, oil industry, various optical devices, medical imaging etc. The objective for exploring current investigation is to disclose the thermal impact of Oldroyd-B nanofluid comprising the buoyancy driven flow. The heat and mass transfer analysis is predicted with insight of Brownian motion and thermophoresis phenomenon. The flow is subject to bidirectional surface maintaining the uniform velocity. The zero-mass constraints are utilized for analyzing the flow phenomenon. The analytical treatment is suggested regarding the computations of developed system. Fundamental of thermal transport phenomenon are suggested with physical aspects. It is observed that velocity profile enhances with applications of buoyancy forces. The temperature profile reduces due to velocity ratio parameter. Current results present applications in cooling processes, thermal management devices, heating control, extrusion processes, chemical systems etc.